2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649649
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reflected green light and infrared photoplethysmography

Abstract: We evaluated the accuracy of pulse rate measurements obtained by reflected green light photoplethysmography (PPG) compared to reflected infrared light photoplethysmography and ECG. The wavelengths of the green and infrared light were 525 and 880 nm, respectively, and experiments were performed at 25 degrees C and at a skin temperature below 15 degrees C. The pulse rate obtained from reflected green light PPG was compared with the ECG RR interval and the pulse rate from reflected infrared PPG. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…By normalizing the modulation, and using wavelengths that have been found to better determine pulsatile blood flow, our present study demonstrated the practical application of a PPG device may be a promising technique as a heart rate monitor. 9,16,20,26,32 To our knowledge this is the first study to examine light wavelength reflectance and skin type influence during both rest and exercise.…”
Section: 36mentioning
confidence: 99%
See 1 more Smart Citation
“…By normalizing the modulation, and using wavelengths that have been found to better determine pulsatile blood flow, our present study demonstrated the practical application of a PPG device may be a promising technique as a heart rate monitor. 9,16,20,26,32 To our knowledge this is the first study to examine light wavelength reflectance and skin type influence during both rest and exercise.…”
Section: 36mentioning
confidence: 99%
“…It is therefore critical that the device penetrate deep enough to provide detection of arterial vessels in order to determine the pulsatile changes in associated volume between systole and diastole. 3,6,8,9,16,20,23,25,26 In the present study, the interaction between various light wavelengths and skin type was investigated at rest and during exercise. We hypothesized that certain wavelengths of light would provide better light reflectance across skin types represented by a greater peak in modulation.…”
mentioning
confidence: 99%
“…PPG signals were measured with various LEDs as the optical source; the primary wavelength is in the range of ~ 935 nm for "infrared", ~ 660 nm for "red", ~ 470 nm for "blue", and ~ 525 nm for "green". However, we will stress the advantages of green-LED-based photoplethysmography in the following discussion because its superior performance [6].…”
Section: Experimental Methods and Setupmentioning
confidence: 99%
“…In trying to noninvasively detect alcohol intake, many studies have focused on optical analysis of the photoplethysmogram (PPG) signal [1][2][3][4][5][6]. This approach is attracting more attention from the viewpoint of its many medical applications [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…This choice is a trade-off and depends on the targeted application, but is usually in the 510 to 940 nm range corresponding to green and infrared lights, respectively. Measurements done on light skins and at normal ambient temperature (around 20 °C) have shown that reflected green light has more desired properties to maintain a good signal to noise ratio during motion compared to IR [66]. This is the main reason many consumer devices that target ambulatory heart rate measurements use green light source.…”
Section: Figurementioning
confidence: 99%